Development of a New Structural Class of Broadly Acting HCV Non‐Nucleoside Inhibitors Leading to the Discovery of MK‐8876. (25th July 2017) - McComas, Casey C.; Palani, Anandan; Chang, Wei; Holloway, M. Katharine; Lesburg, Charles A.; Li, Peng; Liverton, Nigel; Meinke, Peter T.; Olsen, David B.; Peng, Xuanjia; Soll, Richard M.; Ummat, Ajay; et al.
Abstract: Studies directed at developing a broadly acting non‐nucleoside inhibitor of HCV NS5B led to the discovery of a novel structural class of 5‐aryl benzofurans that simultaneously interact with both the palm I and palm II binding regions. An initial candidate was potent in vitro against HCV GT1a and GT1b replicons, and induced multi‐log reductions in HCV viral load when orally dosed to chronic GT1 infected chimpanzees. However, in vitro potency losses against clinically relevant GT1a variants prompted a further effort to develop compounds with sustained potency across a broader array of HCV genotypes and mutants. Ultimately, a biology and medicinal chemistry collaboration led to the discovery of the development candidate MK‐8876. MK‐8876 demonstrated a pan‐genotypic potency profile and maintained potency against clinically relevant mutants. It demonstrated moderate bioavailability in rats and dogs, but showed low plasma clearance characteristics consistent with once‐daily dosing. Herein we describe the efforts which led to the discovery of MK‐8876, which advanced into Phase 1 monotherapy studies for evaluation and characterization as a component of an all‐oral direct‐acting drug regimen for the treatment of chronic HCV infection. Abstract : Both palms open : Studies directed at developing a broadly acting non‐nucleoside inhibitor of HCV NS5B led to the discovery of a novel structural class of 5‐aryl benzofurans that simultaneously interact with both the palm I and palm II binding regions. Herein we describe the efforts that led to the discovery of MK‐8876, which advanced into Phase 1 monotherapy studies for evaluation and characterization as a component of an all‐oral direct‐acting drug regimen for the treatment of chronic HCV infection.